Effects of an Inquiry-Focused, Content-Intensive Program on Pre-Kindergarten-9th Grade Teachers’ Content Knowledge, Self-Efficacy, and Goals - Nugent, Patricia; Friday, Michelle Edgcomb; Evens, Wayne; McConnaughay, Kelly; Morris, Sherrie; Finson, Kevin; Wolffe, Robert; Crowe, Heljä Antola (European Scientific Journal, ESJ, 2017)
This study describes the effects of an inquiry-focused, contentintensive professional development program on Pre-kindergarten-9th grade teachers’ science and mathematics knowledge, use of classroom based inquiry, improvement in their science teaching self-efficacy and other motivation constructs. This two-and-a-half-year program was designed to meet the needs of teachers in a local urban school district. The professional development in the form of a graduate program intentionally sought to emphasize science and mathematics content knowledge and inquiry teaching. Twenty experimental teacher-participants were involved in the program with twelve additional teachers as a control group. Data collection instruments used for this study included content testing, student test-scores, self-efficacy belief surveys, and behavioral scales. The results of the study indicated greater growth for program participants in the areas of science and mathematics content knowledge. The participants also showed greater increases in science teaching self-efficacy as compared to the teachers in the control group.